Policies affecting deforestation for cattle in Central America. - Kaimowitz, D. (1997)
The most important change in land use in Central America in the last 40 years has been the widespread conversion of forest to pasture. The literature presents a number of explanations for this expansion. Depending on which factors are believed to be important, the prognosis and policy recommendations to address the issues will differ. This study uses the Central American experience to put forth some hypotheses about the factors influencing forest conversion to pasture, and about how effective policies have been or are likely to be in addressing the problems arising from conversion. Conclusions drawn from the study indicate that market prices for beef and dairy products, technological change and policies which constrain timber prices have only moderate or little influence on the rate of clearance. However, it was found that road construction, land tenure and land use policies are likely to have a significant impact on the amount of forest that is cut to make way for pasture. It is also recommended that livestock credit also be restricted in agricultural frontier regions with high rainfall.